2015 Joint Urban Remote Sensing Event (JURSE) 2015
DOI: 10.1109/jurse.2015.7120478
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of urban areas by multi-aspect TomoSAR data fusion

Abstract: Recent advances in airborne synthetic aperture radar tomography (TomoSAR) enable the generation of threedimensional point clouds of urban areas with sub-meter accuracy and a point density comparable to LiDAR by exploiting multi-baseline stacks from multiple viewing angles. This paper summarizes the complete workflow from tomographic height reconstruction via geocoding to the combination of multi-aspect point clouds by a novel voxel-space-based fusion strategy. The evaluation results with respect to LiDAR-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This method is computationally more efficient than the one introduced in [42] due to the reduced number of points in the matching step. Relevant work in the airborne research domain can be found in [56] and [57]. It is important to note that all mentioned existing methods perform the point cloud fusion geometrically.…”
Section: Geodetic Fusion Of Tomosar Point Cloudsmentioning
confidence: 99%
“…This method is computationally more efficient than the one introduced in [42] due to the reduced number of points in the matching step. Relevant work in the airborne research domain can be found in [56] and [57]. It is important to note that all mentioned existing methods perform the point cloud fusion geometrically.…”
Section: Geodetic Fusion Of Tomosar Point Cloudsmentioning
confidence: 99%
“…The core parameter of this procedure is the edge length d of the voxel cubes, which basically defines both the resolution of the fused point cloud as well as the degree of data and noise reduction. As has been shown in Schmitt (2015), while the combination of multi-aspect data already helps to fill previously shadowed scene parts, this fusion strategy additionally provides a measurable improvement of the 3D accuracy of the reconstructed 3D points, as well as a significant reduction of the number of points.…”
Section: Fusion Of Point Clouds From Multiple Aspectsmentioning
confidence: 80%
“…For the analysis of urban areas, multi-aspect data fusion has been demonstrated as a viable solution for this problem (e.g. Schmitt, 2015). Therefore, the same approach is used for fusing point clouds of multiple viewing directions in the context of this work.…”
Section: Fusion Of Point Clouds From Multiple Aspectsmentioning
confidence: 99%
See 1 more Smart Citation